Female Urinary Incontinence: Prevalence and Impact on the Quality of Life of Gynaecological Clinic Attendees in Lagos, Nigeria - Akinlusi, FM; Ottun, TA; Oshodi, YA (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the prevalence of urinary incontinence (UI); risk factors; impact on quality of life and symptom specific health seeking behaviour. Methods: A cross-sectional study of 395 women attending gynaecological clinic of the Lagos State University Teaching Hospital. UI was defined as the complaint of any involuntary leakage of urine in the previous six months. Socio-demographic characteristics, obstetrics, gynaecological, medical and surgical risk factors, impact on daily activities and treatment history were assessed. Univariate, bivariate and multivariable analyses were performed. Results: Participants age ranged from 25-67 years with a mean of 38.81 ± 10.1. Prevalence of UI was 32.9%. Urge UI occurred in 18.0% of all respondents while the prevalence of stress and mixed incontinence was 7.3% and 7.6% respectively. Independent risk factors for urinary incontinence were age (OR= 0.49, 95%;CI = 0.26-0.92), higher body mass index (OR = 1.92; 95% CI =1.53-3.00) and history of constipation(OR = 2.11; 95% CI =1.30 - 3.43). About47%of those with UI admitted to having negative feelings such as despair, anxiety and depression while 45% had a cumulative moderate to severe affectation of their quality of life in all domains. Despite these, only 27.7% sought help. Conclusions: Despite thesubstantial impact of UI on the quality of life, majority do not seek help. Addressing modifiable risks factors, improving treatment seeking behaviour by correction of misconceptions and elimination of stigma will go a long way in reducing the prevalence of UI.